2018
DOI: 10.1016/j.exger.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of donor age on organ transplants: A review and implications for aging research

Abstract: Despite the considerable amount of data available on the effect of donor age upon the outcomes of organ transplantation, these still represent an underutilized resource in aging research. In this review, we have compiled relevant studies that analyze the effect of donor age in graft and patient survival following liver, kidney, pancreas, heart, lung and cornea transplantation, with the aim of deriving insights into possible differential aging rates between the different organs. Overall, older donor age is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 74 publications
4
36
0
Order By: Relevance
“…Studies with patients and animal models of kidney transplantation have reported a stronger immune response in recipients with older donors with an elevated occurrence of acute rejection episodes . To the best of our knowledge, we have shown for the first time, similar results in heart transplanted patients.…”
Section: Discussionsupporting
confidence: 71%
“…Studies with patients and animal models of kidney transplantation have reported a stronger immune response in recipients with older donors with an elevated occurrence of acute rejection episodes . To the best of our knowledge, we have shown for the first time, similar results in heart transplanted patients.…”
Section: Discussionsupporting
confidence: 71%
“…The signi cant differences in overall, graft and kidney survival found in the Kaplan-Meier analysis were mainly related to donors' age, which has been con rmed as a risk factor for death [20,21]. However, only a small difference between the smoking and non-smoking donors was found when the donors' age was analyzed by subgroups.…”
Section: Discussionmentioning
confidence: 86%
“…Studies suggest that kidneys from donors over the age of 60 may have suboptimal graft survival, with a three-year graft survival being only 58% [7] while a recent study suggests that the new age of worsening 1 1 1 survival rate has increased to 70 years of age in the same group [8]. Therefore, the donor age is thought to be the most significant factor that can negatively impact graft survival [9]. The kidney profile donor index (KDPI) score has been used to assess the risk of graft loss of any given donor compared to the median population of donors using 10 donor-specific criteria including age, sex, height, weight, history, and duration of hypertension and diabetes, hepatitis C virus (HCV) status, donation after cardiac death (DCD) status, and donor cause of death.…”
Section: Introductionmentioning
confidence: 99%